Abnormal levels of miRNA in pancreatic cancer are linked to tumor progression by regulating the translation of tumor-associated mRNA - Fadian Ding; Yun Zhong; Han Zhang; Denghan Zhang; Zhou Zheng; Xiang Zhang; Guozhong Liu; Shangeng Weng (Annals of Medicine)
Background Pancreatic cancer remains one of the most malignant tumors, characterized by limited treatment efficacy.Main Findings microRNAs (miRNAs) play a crucial role in regulating the proliferation, invasion, migration, drug resistance, apoptosis, and cell cycle progression of pancreatic cancer cells by inhibiting tumor-associated proteins. Metscape analysis revealed that miRNA-targeted proteins associated with pancreatic cancer are enriched in processes such as cell proliferation, mitosis, and cell migration, and participate in multiple signaling pathways. These proteins primarily localize to classical pathways, including JAK/STAT, PI3K/AKT, and Wnt/β-catenin. Furthermore, gene mutations or abnormal alternative poly(A)denylation (APA) within miRNA-targeted regions can disrupt base pairing to the 3’-Untranslated Region (3′-UTR), thereby enhancing the translation of oncogenic mRNA translation.Future Directions Collectively, these findings indicate that multiple miRNAs act cooperatively to influence pancreatic cancer progression. Consequently, therapeutic strategies aimed at restoring the balance of the miRNA system are essential to disrupt the ‘mRNA-oncogene’ vicious cycle.